2007
DOI: 10.1086/518645
|View full text |Cite
|
Sign up to set email alerts
|

The Quiet Sun Network at Subarcsecond Resolution: VAULT Observations and Radiative Transfer Modeling of Cool Loops

Abstract: One of the most enigmatic regions of the solar atmosphere is the transition region ( TR), corresponding to plasmas with temperatures intermediate of the cool, few thousand K, chromosphere and the hot, few million K, corona. The traditional view is that the TR emission originates from a thin thermal interface in hot coronal structures, connecting their chromosphere with their corona. This paradigm fails badly for cool plasmas (%T < 10 5 K ), since it predicts emission orders of magnitude less than what it is ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 51 publications
2
46
0
Order By: Relevance
“…We find cool loops with lengths of 5-10 Mm, but with very low heights (in the range 10 −2 −10 −1 Mm). Loops this low in the solar atmosphere (effectively embedded in the chromosphere) cannot be visible in the Ly-α line; moreover, compared with the observations of Patsourakos et al (2007), our loops typically have lower pressures compared to their estimates.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…We find cool loops with lengths of 5-10 Mm, but with very low heights (in the range 10 −2 −10 −1 Mm). Loops this low in the solar atmosphere (effectively embedded in the chromosphere) cannot be visible in the Ly-α line; moreover, compared with the observations of Patsourakos et al (2007), our loops typically have lower pressures compared to their estimates.…”
Section: Discussionmentioning
confidence: 54%
“…Some recent observations with the VAULT instrument (Very High Angular Ultraviolet Telescope, Korendyke et al 2001) in the H i Ly-α line at very high spatial resolution showed looplike structures with estimated temperatures and densities (T = 10 4 −3 × 10 4 K, P = 0.1−0.3 dyne cm −2 ) that could be appropriate for the low-temperature end of cool loops (Patsourakos et al 2007;Vourlidas et al 2010). While this interpretation has been debated (Judge & Centeno 2008), those observations, together with the persistence of the problem of the excess emission in EUV lines below 10 5 K, call for additional investigations on the matter.…”
Section: Introductionmentioning
confidence: 94%
“…It is still under debate if the TR emission originates from a thin thermal interface connecting the chromosphere and corona (Gabriel 1976;Dowdy et al 1986;Peter 2001), or from isolated unresolved tiny loops (Feldman 1983(Feldman , 1987Feldman & Laming 1994). Recently, Patsourakos et al (2007) reported the first spatially resolved observations of subarcsecond-scale (0.3 ) loop-like structures seen in the Ly-α line, as observed by the Very High Angular Resolution Ultraviolet Telescope (VAULT). As mentioned in that paper, flows can have distinct spectroscopic signatures, which can help to distinguish between the two possibilities of the TR emission origin.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting signal is about 95% pure Lyα emission (Teriaca & Schühle, personal communication). More detail is given in Korendyke et al (2001) and Patsourakos et al (2007).…”
Section: Observations and Measurementsmentioning
confidence: 99%
“…VAULT acquired Lyα images with much higher spatial and temporal resolution than the EUV imagery from the TRACE, SoHO, and STEREO satellites but only for a few minutes. The Lyα fine structure in these images is discussed by Patsourakos et al (2007) and Judge & Centeno (2008).…”
Section: Introductionmentioning
confidence: 99%